Mass extinctions drove increased global faunal cosmopolitanism on the supercontinent Pangaea. Issue 1 (December 2017) - Button, David; Lloyd, Graeme; Ezcurra, Martín; Butler, Richard
Abstract Mass extinctions have profoundly impacted the evolution of life through not only reducing taxonomic diversity but also reshaping ecosystems and biogeographic patterns. In particular, they are considered to have driven increased biogeographic cosmopolitanism, but quantitative tests of this hypothesis are rare and have not explicitly incorporated information on evolutionary relationships. Here we quantify faunal cosmopolitanism using a phylogenetic network approach for 891 terrestrial vertebrate species spanning the late Permian through Early Jurassic. This key interval witnessed the Permian–Triassic and Triassic–Jurassic mass extinctions, the onset of fragmentation of the supercontinent Pangaea, and the origins of dinosaurs and many modern vertebrate groups. Our results recover significant increases in global faunal cosmopolitanism following both mass extinctions, driven mainly by new, widespread taxa, leading to homogenous 'disaster faunas'. Cosmopolitanism subsequently declines in post-recovery communities. These shared patterns in both biotic crises suggest that mass extinctions have predictable influences on animal distribution and may shed light on biodiversity loss in extant ecosystems. Mass extinctions are thought to produce 'disaster faunas', communities dominated by a small number of widespread species. Here, Button et al. develop a phylogenetic network approach to test this hypothesis and find that mass extinctions did increase faunal cosmopolitanism across Pangaea during the late Palaeozoic and early Mesozoic.